Subcritical water extraction of phenolics, antioxidants and dietary fibres from waste date pits. Issue 6 (December 2020) - Li, Bing; Akram, Maham; Al-Zuhair, Sulaiman; Elnajjar, Emad; Munir, Muhammad Tajammal
Graphical abstract: Highlights: SCWE was used to minimize date pits volume and to recover valuable by-products. Effects of process variables on the product yields were investigated. Response surface methodology was used to optimise the extraction yields. Abstract: The growing demand for dates, as food, has enhanced its production and increased the total amount of date pits waste. Subcritical water extraction (SCWE) can be used to effectively extract valuable products from date pits. This study was to extract phenolic compounds, total flavonoid content, antioxidants, and dietary fibres from the date seeds using SCWE. The effects of process variables such as feed mixture concentration ( x ), extraction temperature ( T ), and extraction time ( t ) on the yields of total phenolic content (TPC), total flavonoid content (TFC), antioxidants, and dietary fibres were investigated for process optimisation using desirability approach. The results showed that extraction temperature could significantly increase TPC, TFC, and dietary fibres extraction yields, but has less effect on the antioxidant extraction. The feed mixture concentration has shown a significant effect on antioxidant extraction but was insignificant on TPC, TFC, and dietary fibres extractions. The desirability approach of process optimisation validated the feasibility of using SCWE for valuable products extraction from date pits.